2009
DOI: 10.1002/adsc.200900590
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Arylphosphonates by Palladium(0)‐Catalyzed Cross‐Coupling in the Presence of Acetate Additives: Synthetic and Mechanistic Studies

Abstract: An efficient protocol for the synthesis of arylphosphonate diesters via a palladium-catalyzed cross-coupling of H-phosphonate diesters with aryl electrophiles, promoted by acetate ions, was developed. A significant shortening of the cross-coupling time in the presence of the added acetate ions was achieved for bidentate and monodentate supporting ligands, and for different aryl electrophiles (iodo, bromo and triflate derivatives). The reaction conditions were optimized in terms of amount of the catalyst, suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
87
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(89 citation statements)
references
References 68 publications
1
87
0
Order By: Relevance
“…A two-step transformation by treatment of 4 with PBr 5 followed by esterification furnished the diethyl 4-bromopyridine-2,6-dicaboxylate (5). Cross-coupling of 5 with diethyl phosphite under Stawinski's conditions [10] afforded the phosphonate 6 in 80% yield. Attempted hydrolysis of 6 was problematic for this particular substrate although hydrolysis of ester is an easily occurring transformation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A two-step transformation by treatment of 4 with PBr 5 followed by esterification furnished the diethyl 4-bromopyridine-2,6-dicaboxylate (5). Cross-coupling of 5 with diethyl phosphite under Stawinski's conditions [10] afforded the phosphonate 6 in 80% yield. Attempted hydrolysis of 6 was problematic for this particular substrate although hydrolysis of ester is an easily occurring transformation.…”
Section: Resultsmentioning
confidence: 99%
“…Preparation of phosphonate 6 [10] To a 25 mL Schlenk tube equipped with a magnetic bar was added Pd(OAc) 2 (3.4 mg, 0.015 mmol), dppf (16.6 mg, 0.03 mmol) and KOAc (6.4 mg, 0.065 mmol). The tube was then evacuated (10 min×3) under vacuum and backfilled with Ar.…”
Section: General Methodsmentioning
confidence: 99%
“…They were inferior to Pd(PPh 3 ) 4 in the terms of the reaction time and yield of the cross-coupling product (entries [12][13][14][15][16]. The screening of solvent showed that the reaction proceeded effectively in dioxane (94%), 1,2-dichloroethane (DCE) (78%), 1,2-dimethoxyethane (DME) (75%) and tetrahydrofuran (THF) (71%) whereas toluene, CH 3 CN, N-methylpyrrolidone (NMP) and EtOH gave inferior results (entries [17][18][19][20][21][22][23]. The addition of a base such as triethylamine to facilitate the Hirao reaction decreased the yield of the coupling product (10) (38%).…”
Section: Resultsmentioning
confidence: 99%
“…The Pd-catalyzed P-arylation of aryl halides with dialkyl H-phosphites is promoted by acetate ions, and ArPdOAc (C) is the key intermediate for reaction mechanism. 12,13,19) The ligand exchange of ArPdOAc (C) with dialkyl H-phosphite (9) gives ArPdP(O)(OR) 2 intermediate D, which undergo reductive elimination to form the coupling product and regenerate the Pd(0) species (A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation